3-Methylhistidine excretion as an index of myofibrillar protein catabolism in neuromuscular disease. - McKeran, R O (1979)
Myofibrillar protein catabolism has been calculated in a variety of neuromuscular diseases from the amount of 3-methylhistidine excreted in the urine. It was found to be significantly raised in Duchenne type muscular dystrophy, motor neurone disease, polymyositis, and thyrotoxic myopathy. In Becker type muscular dystrophy the level was slightly raised. It was normal in scapuloperoneal and limb girdle dystrophy, dystrophia myotonica, extrapyramidal disease, and multiple sclerosis. It was significantly decreased in hypothyroid myopathy.